ISLAMIC BANKING EFFICIENCY: A SYSTEMATIC LITERATURE REVIEW - Siti Maryam Idris; Fadzila Azni Ahmad (Journal of Islamic, Social, Economics and Development, 2020)
Efficiency has been measured through many approaches in banking system. For instance, it has been measured through scale efficiency, technical efficiency and pure technical efficiency. However, efficiency is not focusing on the three types of efficiency as mentioned above. Efficiency in banking can be interprets as the controlling cost of banking while the production and profit are maximised. Efficiency is important in banking operation because it would determine the stability of the banking. However, majority of past researches regarding efficiency only focus on conventional banking. As conventional banking established before Islamic banking, the efficiency of conventional banking is higher compare to Islamic banking. The questioned raised, do the years of establishment is a factor that contributes to efficiency? What are the other factors that may influence efficiency in Islamic banking? Therefore, this study would like to determine efficiency in Islamic banking through systematic literature review. Second objective is to analyse the determinants of efficiency in Islamic banking. The methodology comprises of explanatory research design. Data collection solely based on secondary data. Data obtained through documentation review using systematic literature review. Expected findings of this study includes the reviews and discussion on Islamic banking efficiency. This study would help researchers and Islamic banking to focus on efficiency management and to emphasize the importance of efficiency in Islamic banking.